Designing And Developing Smart Plant Information System - Kasmin, Fauziah; Othman, Zuraini; Syed Ahmad, Sharifah Sakinah; Munuganan, Previna; Roslan, Muhammad Naim Syahmi; Thinagaran, Paveetheran; Shafie, N.I. (Penerbit Universiti Teknikal Malaysia Melaka, 2021)
The COVID-19 pandemic has undoubtedly impacted the way of life of all people in the world. The effect continues to worsen especially when our government imposed lock downs where everyone was required to stay home. Due to a long period of staying at home, boredom becomes one of the most reported negative psychological effects of quarantine. It is undeniable that people of all ages enjoy gardening and planting. Hence, this time during the pandemic can be a golden opportunity for people to get outside of their compound and grow their interest in gardening. Thus, this smart plant information system is designed to introduce the basic knowledge of plantations more easily and effectively. The system is applicable for multiple users who tend to learn more about plants and their plantation methods. Both men and women can start their garden with proper planting methods. This system has been developed using several modules such as leaf recognition using convolutional neural network (CNN), plant disease advice using knowledge-based expert system, and plant information using a chatbot. The leaf recognition using the CNN module will help the user recognize a plant by providing the plant’s leaf image. The plant disease advice will diagnose certain diseases a plant might have by calculating the confidence level of provided symptoms of the disease. Finally, plant information using the chatbot module will provide information about plants by answering the user’s questions. It is hoped that this system could serve as the best smart plant information system for the users.